The Philosophy of Psychology. - O'Donohue, William (Sage Publications, 1996)
This major text provides the first comprehensive anthology of the key topics arising in the philosophy of psychology. Bringing together internationally renowned authors, including Herb Simon, Karl Pribram, Joseph Rychlak, Ullin T Place and Adolf Gr[um]unbaum, this volume offers a stimulating and informative addition to contemporary debate. With the cognitive revolution of the 1960s, there has been a resurgence of interest in the study of the philosophical assumptions and implications of psychology. Several significant themes, such as the foundations of knowledge, behaviourism, rationality, emo.